2002
DOI: 10.1046/j.1439-0531.2002.00377.x
|View full text |Cite
|
Sign up to set email alerts
|

Low Dose Insemination in the Sow – A Review

Abstract: Artificial insemination (AI) in pigs has been established for about four decades but ejaculates are still used insufficiently. Higher demand of semen for AI and new techniques that involve low sperm concentration require the optimization of insemination protocols. Based on the knowledge of the physiology of sperm transportation and events in the female genital tract prior to fertilization, new strategies are under development to minimize sperm losses. One goal is to deposit the semen into the uterine horn rath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
6

Year Published

2005
2005
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 32 publications
0
33
0
6
Order By: Relevance
“…There are two procedures for depositing spermatozoa into the pig uterus: surgically [37,38] or nonsurgically. An intrauterine AI with low numbers of spermatozoa is surgically accomplished by placing a small semen volume (0.5 mL) close to the uterotubal junction of each uterine horn [39].…”
Section: Sperm Parametersmentioning
confidence: 99%
“…There are two procedures for depositing spermatozoa into the pig uterus: surgically [37,38] or nonsurgically. An intrauterine AI with low numbers of spermatozoa is surgically accomplished by placing a small semen volume (0.5 mL) close to the uterotubal junction of each uterine horn [39].…”
Section: Sperm Parametersmentioning
confidence: 99%
“…The high number of sperm needed for a satisfactory result is partly a consequence of the anatomy of the reproductive organs of the sow, with very long uterus horns, and partly because of large losses of live sperm during storage and transport and also after insemination. Therefore, low dose insemination techniques (with a minimum of 50 million spermatozoa per dose) such as deep-uterine insemination (DUI) have been developed (Rath, 2002). Hedeboe et al (2004) have shown that sows that were inseminated with this technique showed no differences in pain reactions and scratches in the mucosa of the cervix compared to the conventional methods.…”
Section: Sperm Sexingmentioning
confidence: 99%
“…After IUAI, up to 30% of spermatozoa are excreted retrogradely in the pig [35] and are detected in the vaginal smears of tammars and possums [2]. Tammar spermatozoa are also broken down in the tract by phagocytosis [16].…”
Section: Discussionmentioning
confidence: 99%